Biology and Management of Oxalis (Oxalis stricta) in Ornamental Crop Production: ENH1253/EP514, 2/2015 - Lollar, Matthew; Marble, Chris (EDIS, 2015)
Oxalis grows throughout the year in Florida. It can be found growing in sidewalk cracks, alongside trails, in lawns, flower beds, cultivated fields, and in container nursery stock. In greenhouse studies, oxalis populations have been shown to negatively impact the growth rates of ornamental crops. This 6-page fact sheet was written by Matt Lollar and Chris Marble, and published by the UF Department of Environmental Horticulture, February 2015. (Photo: Chris Marble) ENH1253/EP514: Biology and Management of Oxalis (Oxalis stricta) in Ornamental Crop Production (ufl.edu)